The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1104/pp.114.4.1523
|View full text |Cite
|
Sign up to set email alerts
|

Cell Wall Metabolism in Ripening Fruit (IX. Synthesis of Pectic and Hemicellulosic Cell Wall Polymers in the Outer Pericarp of Mature Green Tomatoes (cv XMT-22)

Abstract: Discs of outer pericarp were excised from mature green tomato (Lycopersicon esculentum Mill.) fruit and kept in sterile tissue culture plates for 4 d, including 2 d of incubation with D-[U-'3C]glucose. Cell walls were prepared and the water-soluble, pectic, and hemicellulosic polymers were extracted. Cell wall synthetic capacity was determined by gas chromatography-mass spectrometry analysis of incorporation of the heavy isotope label. l h e "outer" 2-mm pericarp region, which included the cuticle, had a lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 33 publications
0
16
0
1
Order By: Relevance
“…We monitored the relative incorporation of 13 C into the Glc detected in the cellulose fraction, using gas chromatography-mass spectrometry analysis of alditol acetates generated after hydrolysis of the cellulose fraction. Selective ion monitoring mode, as described previously (Greve and Labavitch, 1991;Huysamer et al, 1997), indicated that CESTRIN significantly decreased the amount of [ 13 C]Glc that was incorporated into the cellulose fraction; this reduction was greater when more CESTRIN was applied (P , 0.00001 for 15 mM, P = 0.000124 for 8 mM) in our short-term treatment (Table II). In addition, a less profound but still significant reduction was observed in the 2 N trifluoroacetic acid (TFA)-hydrolyzed cell wall fraction (i.e.…”
Section: Cestrin Inhibits Cell Elongation and Reduces Cellulose Contentmentioning
confidence: 86%
See 2 more Smart Citations
“…We monitored the relative incorporation of 13 C into the Glc detected in the cellulose fraction, using gas chromatography-mass spectrometry analysis of alditol acetates generated after hydrolysis of the cellulose fraction. Selective ion monitoring mode, as described previously (Greve and Labavitch, 1991;Huysamer et al, 1997), indicated that CESTRIN significantly decreased the amount of [ 13 C]Glc that was incorporated into the cellulose fraction; this reduction was greater when more CESTRIN was applied (P , 0.00001 for 15 mM, P = 0.000124 for 8 mM) in our short-term treatment (Table II). In addition, a less profound but still significant reduction was observed in the 2 N trifluoroacetic acid (TFA)-hydrolyzed cell wall fraction (i.e.…”
Section: Cestrin Inhibits Cell Elongation and Reduces Cellulose Contentmentioning
confidence: 86%
“…Cell wall materials were isolated into AIR (Günl et al, 2010). The AIR remaining insoluble after a 1-h 2 N TFA hydrolysis at 121°C (cellulose fraction) was collected by centrifugation, dissolved by stirring overnight in 15 N TFA at room temperature, and then hydrolyzed in 5 N TFA for 1 h. The 2 N and 15 N TFA fractions were derivatized into alditol acetates as described previously (Greve and Labavitch, 1991;Huysamer et al, 1997). Gas chromatographymass spectrometry analysis was carried out as described previously in the selective ion monitoring mode to determine the relative incorporation of [ 13 C] Glc.…”
Section: C]glc Incorporation Assay and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent steps in preparing crude cell wall samples (alcohol-insoluble solids [AISs]) were also as in Huysamer et al (1997), ending with two washes of the wall pellets with acetone and drying in a vacuum oven. Starch was removed by incubating 200 mg of AIS with 40 units each of a-amylase (from porcine pancreas, Sigma-Aldrich) and pullulanase (from Bacillus acidopullulyticus, Novozymes Biologicals) in 20 mL of Tris-HCl pH 7.0, 0.1% NaN 3 , for 24 h. Neutral sugar composition of the AIS was determined by gas-liquid chromatography as in Campbell et al (1990).…”
Section: Cell Wall Analysismentioning
confidence: 99%
“…Cell walls were prepared from 50 g of diced outer pericarp of AC and DFD fruit (MG and RR stages) by boiling the pericarp pieces in 95% ethanol for 30 min to prevent autolytic activity, as described in Huysamer et al (1997). Subsequent steps in preparing crude cell wall samples (alcohol-insoluble solids [AISs]) were also as in Huysamer et al (1997), ending with two washes of the wall pellets with acetone and drying in a vacuum oven.…”
Section: Cell Wall Analysismentioning
confidence: 99%